SUCCESS IN LEARNING ENGLISH: THE STUDENTS’ DEFINITION - AGUS WAHYUDI (Sriwijaya University Learning and Education International Conference, 2016)
Individual learner differences and success in learning English are not new topics.Many researches were conducted to find out the personal characteristics of learnerthat make one learner more successful than another. Defining success is a difficult,but every student has their own definition of what success in learning English is.Inspired by Mardiah (2015) research about success in second language learning, thispaper is aimed in describing the definition of success in learning English fromstudents’ point of view and their arguments behind it. The respondent of thisresearch is Public Health students of STIK Bina Husada Palembang who tookEnglish subject. The definitions are classified into three categories; know the basicrule of the language, speak fluently like native speaker, and use the language tocommunicate. The definition and its argument reflect the students’ goal in learningEnglish.